(untitled) (Bangladesh Heart Journal, 2016)
Cardiopulmonary bypass (CPB) assisted open heart surgery have become a frequent surgical procedures in almost all major heart surgeries. However,growing evidence indicates that anemia, coagulation derangements, platelet dysfunction and inflammatory responses are common in patients undergoing CPB aided cardiac surgery. The aim of the present study was to characterize CPB induced hematologic changes in patients undergoing cardiac surgery. A total of sixty three patients undergoing elective cardiac surgery in the department of Cardiac Surgery, BSMMU, Dhaka, Bangladesh, were prospectively randomized into the present study: 33 of which underwent CPB aided cardiac surgery (CPB-aided) and the rest 30 patients underwent cardiac surgery without CPB (CPB non-aided). Complete blood count together with Hb%, prothrombin time (PT) and International normalized ratio (INR) was determined preoperatively and on 1st, 3rd and 7th postoperative days (POD). The TC of WBC was significantly higher in CPB aided patients than that of CPB non-aided patients on 1st POD. When comparison was done, total count of RBC, platelets & Hb% were significantly lower in CPB aided patients compared to patients underwent cardiac surgery without CPB on the 7th POD. Additionally, PT and INR were higher in CPB aided cardiac patients compared to that of CPB non-aided patients on the 7th POD. The lower levels of Hb% and TC of RBC following CPB-aided cardiac surgery may be due to excessive hemolysis because of mechanical force during extra-corporal circulation. The observed significant leucocytosis in the present CPB aided cardiac surgery patients on 1st POD may support the notion that CPB induces a systemic inflammatory response following cardiac surgery. Further studies are required to evaluate the mechanisms of CPB- induced hematological changes following major cardiac surgery. Bangladesh Heart Journal 2015; 30(2) : 53-57